DEVELOPMENT OF VIBERNIPA LEARNING MEDIA IN PANCASILA VALUE MATERIALS - Mifta Jannah; Ida Putri Rarasati; Muhammad Iqbal Baihaqi (Universitas Islam Balitar, 2017)
This research is in the background by the low activity of students. The purpose ofthis research is to improve activities and by developing Pancasila values using video.This research uses Research and Development (R & D). Desaign and Developmentmethods are also defined as a research method used to produce certain products,and test the effectiveness of the product. Data collection techniques by observingstudents' interest in learning. The data collection tool is by means of a video conceptobservation guide. The collected data is then analyzed by analysis of research anddevelopment.The results of the research are shown on the material aspects and 4.2 on themedia aspects 4.4 On aspects of the language 4.0 according to the module eligibilitycriteria that the module is appropriate to use. The validation results indicated that themodule was able to influence students' learning interest as much as 4.2. This issupported by student observation sheets that show interest in the use of the moduleas many as 6 students feel interested and helped in carrying out learning. It is hopedthat this study will contribute towards development and progress to support theachievement of the FKIP UNISBA vision and mission.